Clinical appearance of oral lesions in bronchial asthma patients using inhalation drug - Vieri, Audrey Amber; Wihardja, Rosiliwati; Dewi, Tenny Setiani (Universitas Padjadjaran, 2020)
Introduction: Inhalation therapy has become the first-line treatment for bronchial asthma patients. Studies have proved that not all of the inhaled drugs reach the target organ, but mostly are deposited in the mouth and cause local immunosuppressant and decrease saliva secretion. These conditions are closely linked to some adverse effects in the mouth. The purpose of this study was to describe the clinical appearance of oral lesion in bronchial asthma patients using inhalation drugs. Methods: This study was descriptive and conducted on 30 bronchial asthma patients that have been using inhalation drug for at least one year, free of other systemic diseases, not using denture and orthodontic appliances. Oral mucosa was examined, and any oral lesion was recorded. Results: The most number of oral lesions found in patients through clinical examinations were plaque (73.3%), followed by a fissure (36.7%), atrophy (30%), and the least oral lesions found were pigmentation (3.3%), bullae (3.3%), and petechiae (3.3%). The lesions found in patients using inhalation drugs in a range of up to 10 years were found more varyingly. Conclusion: Plaque, fissure, atrophy, pigmentation, bullae, and petechiae are oral lesions that are clinically found in bronchial asthma patients using inhalation drugs.